2020
DOI: 10.3390/su12083222
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Impact of Decoupled Payments on Farm Production in Northern Ireland: An Instrumental Variable Fixed Effect Approach

Abstract: The production stimulating impact of agricultural subsidies has been a well-debated topic in agricultural policy analysis for some decades. In light of the EU reform of the Common Agricultural Policy (CAP) in year 2005 in which agricultural subsidies were decoupled from current production decisions and the modification to this payment in 2015, this study investigates the impact of decoupled payments under these two reforms on livestock production in Northern Ireland. The study uses a farm-level panel dataset c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Being convinced of the rising value of their farm's assets, they make riskier decisions (Roche and Mcquinn 2004). As reported Olagunju et al (2020) direct payments exert a 'wealth effect' on the agricultural production process by encouraging farmers to engage in 'riskier' production activities.…”
Section: Resultsmentioning
confidence: 99%
“…Being convinced of the rising value of their farm's assets, they make riskier decisions (Roche and Mcquinn 2004). As reported Olagunju et al (2020) direct payments exert a 'wealth effect' on the agricultural production process by encouraging farmers to engage in 'riskier' production activities.…”
Section: Resultsmentioning
confidence: 99%
“…Tranter et al ( 2007 ) research was based on the potential impacts of the SFP; hence, a lot of the impacts were based off assumptions; thus, follow‐up research is necessary to quantify and discuss the observed impacts of the policy. Olagunju et al ( 2020 ) suggest that the decoupled payments have negatively impacted production levels in Northern Ireland (NI) as the range of production levels in the country widens. As these observations and calculations have been made on a small‐scale, the full‐scale impact of the SFP remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…In the EU context, previous studies have found differentiated impacts of policy reforms on productivity. For example, a shift from production-coupled subsidies to a decoupling regime was found to influence productivity positively [24][25][26], indicating that policies that align farmers' production decisions with the demands of the market enhance productivity. Also, policies aimed at supporting investments that embody innovations tend to facilitate productivity [27].…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%